2014
DOI: 10.1051/0004-6361/201424064
|View full text |Cite
|
Sign up to set email alerts
|

Spectral properties of the largest asteroids associated with Taurid Complex

Abstract: Context. The Taurid Complex is a massive stream of material in the inner part of the Solar System. It contains objects spanning the range of 10 −6 -10 3 m, considered by some authors to have a common cometary origin. The asteroids belonging to Taurid Complex are on Apollo type orbit, with most of them being flagged as potentially hazardous asteroids. In this context, understanding the nature and the origin of this asteroidal population is not only of scientific interest but also of practical importance. Aims. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 57 publications
3
28
1
Order By: Relevance
“…Popescu et al (2011) also find this NEO to be Sr class based on near infrared data. Asteroid 1984 KB was classified as S-class by Bell et al (1988) and Sq by Popescu et al (2014). Again, our classification of K/Sq places this object firmly within the S-complex of asteroids, and is consistent with the previous research.…”
Section: Neos Classification Based On the Shape Of Their Spectrumsupporting
confidence: 90%
See 2 more Smart Citations
“…Popescu et al (2011) also find this NEO to be Sr class based on near infrared data. Asteroid 1984 KB was classified as S-class by Bell et al (1988) and Sq by Popescu et al (2014). Again, our classification of K/Sq places this object firmly within the S-complex of asteroids, and is consistent with the previous research.…”
Section: Neos Classification Based On the Shape Of Their Spectrumsupporting
confidence: 90%
“…An X-class classification is no surprise, as the X-complex comprises of E, M and P-class asteroids, all of which show a moderate red slope with no spectral features that can only be differentiated by albedo knowledge. This exactly describes comet Popescu et al (2014) we see a strong preference for S-complex asteroids in Taurid-like orbits. Two further objects from their sample are part of our 'Group 1' list, with the most secure association with the Taurids: (4183) Cuno and (4486) Mithra, found to be Q and Sq type respectively.…”
Section: Neos Classification Based On the Shape Of Their Spectrumsupporting
confidence: 59%
See 1 more Smart Citation
“…So far, the efforts in finding traces of the common origin of the largest Taurid complex bodies gave rather sceptical results. Popescu et al (2014) studied the spectral properties of the largest asteroids associated with the Taurid complex, but found no evidence supporting mutual relation. Similarly, the spectroscopic and photometric measurements of Tubiana et al (2015) found no apparent link between comet 2P/Encke, the Taurid complex NEOs, and the Maribo and Sutter's Mill meteorites.…”
Section: Introductionmentioning
confidence: 99%
“…Many proposed associations can be therefore just random coincidences. Indeed, the spectra of six large asteroids proposed as members of the Taurid complex showed that five of them are inconsistent with a cometary origin (Popescu et al 2014).…”
Section: Introductionmentioning
confidence: 99%